3D bioprinting of multi-layered segments of a vessel-like structure with ECM and novel derived bioink - Potere, Federica; Belgio, Beatrice; Croci, Giorgio Alberto; Tabano, Silvia; Petrini, Paola; Dubini, Gabriele; Boschetti, Federica; Mantero, Sara (Frontiers in Bioengineering and Biotechnology, 2022)
3D-Bioprinting leads to the realization of tridimensional customized constructs to reproduce the biological structural complexity. The new technological challenge focuses on obtaining a 3D structure with several distinct layers to replicate the hierarchical organization of natural tissues. This work aims to reproduce substitutes compliant with the original tissue, combining the advantages of the 3D bioprinting, decellularization, and accounting for the presence of different cells. The decellularization process was performed on porcine aortas. Various decellularization protocols were tested and evaluated through DNA extraction, quantification, and amplification by PCR to define the adequate one. The decellularized extracellular matrix (dECM), lyophilized and solubilized, was combined with gelatin, alginate, cells to obtain a novel bioink. Several solutions were tested, tuning the percentage of the components to obtain the adequate structural properties. The geometrical model of the large vessel constructs was designed with SolidWorks, and the construct slicing was done using the HeartWare software, which allowed generating the G-Code. The final constructs were 3D bioprinted with the Inkredible+ using dual print heads. The composition of the bioink was tuned so that it could withstand the printing of a segment of a tubular construct up to 10 mm and reproduce the multicellular complexity. Among the several compositions tested, the suspension resulting from 8% w/v gelatin, 7% w/v alginate, and 3% w/v dECM, and cells successfully produced the designed structures. With this bioink, it was possible to print structures made up of 20 layers. The dimensions of the printed structures were consistent with the designed ones. We were able to avoid the double bioink overlap in the thickness, despite the increase in the number of layers during the printing process. The optimization of the parameters allowed the production of structures with a height of 20 layers corresponding to 9 mm. Theoretical and real structures were very close. The differences were 14% in height, 20% internal diameter, and 9% thickness. By tailoring the printing parameters and the amount of dECM, adequate mechanical properties could be met. In this study, we developed an innovative printable bioink able to finely reproduce the native complex structure of the large blood vessel.